Traditional Suona Performance in Henan Province - Li Chen, Li; Manoon Tho-ard, Manoon (วารสารปรัชญาปริทรรศน์, 2026)
This study investigates the historical evolution and regional differentiation of the suona (a traditional Chinese double-reed wind instrument), with a particular focus on the stylistic formation and contemporary development of the Henan suona tradition. The primary objective is to analyze how regional cultural ecology has shaped performance styles and transmission systems, and how Henan suona has maintained continuity while adapting to modern contexts. A qualitative research design was employed, integrating ethnographic fieldwork, archival research, and performance analysis. The research population comprised suona performers, intangible cultural heritage inheritors, and members of folk drum music troupes in selected regions of Henan Province. A purposive sampling strategy was used to select key informants with extensive performance experience and transmission roles. Data collection instruments included semi-structured interviews, participant observation in live performances and rehearsals, and documentary analysis of historical records and musical materials. The collected data were analyzed using thematic analysis to identify patterns related to stylistic characteristics, inheritance mechanisms, and contemporary transformations. The findings reveal that Henan suona performance is centered on the “Ka play” technique, which functions as a core expressive mode shaping its distinctive musical identity characterized by high-pitched, rugged, and passionate sonic qualities. Its transmission system relies heavily on oral and mental teaching within familial lineages and folk drum ensembles, facilitating intergenerational transfer of embodied performance knowledge. In contemporary contexts, Henan suona demonstrates a process of “creative transformation,” as performers increasingly engage with modern stage production, digital media dissemination, and cross-disciplinary collaborations while preserving core aesthetic principles. These developments indicate a dynamic balance between tradition and innovation, offering empirical insights into the resilience and adaptive mechanisms of intangible cultural heritage in China.